A disseminated Mycobacterium marinum infection in a renal transplant HIV-infected patient successfully treated with a bedaquiline-containing antimycobacterial treatment: A case report. (June 2021) - Meybeck, Agnès; Tetart, Macha; Baclet, Véronique; Alcaraz, Isabelle; Blondiaux, Nicolas; Peytavin, Gilles; Veziris, Nicolas; Robineau, Olivier; Senneville, Eric
Highlights: Mycobacterium marinum disseminated infections occur rarely in immunocompromised patients. Treatment of M. marinum infections requires a prolonged multi-drug regimen. Side effects and drug–drug interaction are frequent with a concomitant regimen. Bedaquiline may be an alternative treatment for M. marinum infections. Abstract: Background: Disseminated Mycobacterium marinum infections occur rarely, in immunocompromised patients. Treatment with a prolonged multi-drug regimen exposes patients to drug–drug interactions and side effects. Case report: We report a case of disseminated M. marinum infection in a 54-year-old renal transplant, HIV-infected woman. Manifestations of the infection were cutaneous and subcutaneous nodules, mediastinal lymph nodes and left pulmonary infiltrate. Empirical treatment for non-tuberculous mycobacteria was initiated with rifabutin, ethambutol and azithromycin. After identifying M. marinum in sputum, due to unfavourable clinical evolution and severe drug-related adverse events, treatment was changed to doxycycline and rifabutin. Digestive and haematologic side effects motivated a change in antimycobacterial treatment to a combination of moxifloxacin and bedaquiline. Tolerance was satisfactory, and the patient was cured after 12 months of treatment. Conclusion: We report (to the authors' knowledge) the first case of disseminated M. marinum infection successfully treated with a bedaquiline-containing regimen. Bedaquiline could be an alternative to recommended antimicrobial regimens in cases of non-tuberculous mycobacterial disease, including M. marinum infection.